Civil Conflict and antipoverty programmes: effects on demobilisation (2015)
Antipoverty programmes have been successful in helping millions of people afford betterlivelihoods -- While this is well known, little research has yet been conducted that examines the power of such programmes to influence outcomes in times of conflict, especially in countries where antipoverty programmes are implemented amidst disputes against illegal armed groups -- This paper focuses on the implementation of Familias en Accion, a flagship antipoverty programme in Colombia during the early 2000s when the country was experiencing the crudest peak in its long-lasting internal conflict -- Our estimations are based on a natural experiment that resulted from the rolling out of the programme which allowed us to identify a difference-in-differences approach -- Our results indicate that the programme had positive effects on the demobilisation of combatants -- The theoretical transmission channels of these effects are discussed and contrasted with the existing empirical evidence